Fibrinolysis and Fibrinogenolysis in Disseminated Intravascular Coagulation - Takahashi, Hoyu; Tatewaki, Wataru; Wada, Ken; Niwano, Hiroe; Shibata, Akira (Thrombosis and Haemostasis, 1990)
In order to assess precisely the fibrinolytic state in disseminated intravascular coagulation (DIC), plasma levels of fibrinogenolysis products (FgDP), fibrinolysis products (FbDP) and fibrinogenolysis plus fibrinolysis products (TDP) were measured with newly developed enzyme-linked immunosorbent assays based on monoclonal antibodies in 72 patients with DIC at presentation. Not only FbDP and TDP but also FgDP were markedly elevated in patients with DIC. When analyzed according to the underlying disease categories, the relative proportion of FgDP to TDP was high in patients with acute promyelocytic leukemia and vascular diseases, and it was the lowest in patients with sepsis. Correlation analysis revealed that plasma levels of FgDP correlated negatively with alpha 2-antiplasmin and positively with plasmin-alpha 2-antiplasmin complex (PAP) and a ratio of PAP to thrombin-antithrombin III complex (TAT). These findings indicate that besides fibrinolysis, fibrinogenolysis is markedly accelerated in the majority of the patients with DIC.